1991
DOI: 10.1021/bi00245a005
|View full text |Cite
|
Sign up to set email alerts
|

Transient intermediates in the folding of dihydrofolate reductase as detected by far-ultraviolet circular dichroism spectroscopy

Abstract: The kinetics of the reversible folding and unfolding of Escherichia coli dihydrofolate reductase have been studied by stopped-flow circular dichroism in the peptide region at pH 7.8 and 15 degrees C. The reactions were induced by concentration jumps of a denaturant, urea. The method can detect various intermediates transiently populated in the reactions although the equilibrium unfolding of the protein is apparently approximated by a two-state reaction. The results can be summarized as follows. (1) From transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
157
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(183 citation statements)
references
References 46 publications
25
157
1
Order By: Relevance
“…3A) and it probably originates from an altered environment of the tryptophan and/or of tyrosine residues at the stage of the folding intermediate (Kiefhaber et al, 1990~). Ordering of aromatic residues can contribute significantly to the CD of native proteins near 230 nm (Adler et al, 1973;Manning & Woody, 1989;Khan et al, 1989;Kuwajima et al, 1991). Spectra recorded after 20 s and after 10 min of refolding, when the additional formation of the intermediate via the slow reaction (7 = 170 s) is complete (cf.…”
Section: Time Course Of the Folding Intermediatementioning
confidence: 99%
“…3A) and it probably originates from an altered environment of the tryptophan and/or of tyrosine residues at the stage of the folding intermediate (Kiefhaber et al, 1990~). Ordering of aromatic residues can contribute significantly to the CD of native proteins near 230 nm (Adler et al, 1973;Manning & Woody, 1989;Khan et al, 1989;Kuwajima et al, 1991). Spectra recorded after 20 s and after 10 min of refolding, when the additional formation of the intermediate via the slow reaction (7 = 170 s) is complete (cf.…”
Section: Time Course Of the Folding Intermediatementioning
confidence: 99%
“…Stopped-flow circular dichroism studies showed that a large amount of secondary structure is formed in the dead time (milliseconds time range) of the observation. This has been observed for proteins such as ␣-lactalbumin and lysozyme (5), dihydrofolate reductase (6), and holocytochrome c (7). On the other hand, when using pulsed proton exchange followed by NMR identification of the protected protons, the formation of stable secondary structure elements could be detected over a slower observable time range (8,9).…”
mentioning
confidence: 92%
“…1-5 Earlier studies have revealed that small globular proteins often populate compact intermediates with varying degrees of secondary structure within milliseconds of initiating the refolding reaction, long before they encounter the rate-limiting step of the folding reaction (e.g., refs. [6][7][8][9]. Direct observation of the formation of these early intermediates has, however, been difficult mainly due to the limited temporal resolution of conventional mixing devices.…”
Section: Introductionmentioning
confidence: 99%